MIGRATION SECURITY AS A COMPONENT OF CORPORATE SECURITY: MIGRATION SECURITY AS A COMPONENT OF CORPORATE SECURITY - Metodieva, Tsvetelina; Simeonova, Iliana (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2024)
A new element has been added to the components of corporate security - migration security. The proposed new author's terms for our scientific community - "migration security" will facilitate future research in the field of the impact of migration processes on the security of regions and business organizations.